High temperature permittivity measurements of selected industrially relevant ores: Review and analysis. (1st January 2020) - Bobicki, E.R.; Pickles, C.A.; Forster, J.; Marzoughi, O.; Hutcheon, R.
Highlights: Knowledge of permittivities necessary for scale-up of microwave processes. Cavity perturbation technique used for high temperature permittivity measurements. Permittivity measurements of eight industrially relevant ores discussed. Temperature, frequency, calcination and composition modulate ore permittivity trends. Abstract: The mineral processing and extractive metallurgy industries are under increasing pressure to develop more energy efficient and sustainable technologies. As a result, there is increasing interest in the application of alternative energy sources, such as microwave technology. While bench scale testing has been conducted in this area for over thirty years, scale-up has remained a key challenge. One barrier to implementation has been the lack of understanding of the fundamental interaction of microwaves with ores. Key parameters include the real and the imaginary permittivities, which influence both the heating rate and the microwave penetration depth. Over the last decade, high temperature permittivity measurements have been performed on various ores using the cavity perturbation technique. In this paper, this permittivity data is presented as a function of temperature primarily at 912 MHz. Based on the interpretation of this data, recommendations are made for the sustainable utilization of microwave technology in metallurgical processing.